UPAYA PENINGKATAN PENDAPATAN PAJAK AIR PERMUKAAN OLEH BADAN PENDAPATAN DAERAH PROVINSI RIAU TAHUN 2019 - Ananda, Ryantama; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Tax is the main source of state revenue which has an important role in improving and implementing National Development with the aim of Community Improvement and Prosperity. Surface water tax is a tax on the extraction and/or utilization of surface water. Surface water is all water found on the ground surface. The purpose of this study was to determine the efforts made by the Regional Revenue Agency of Riau Province in increasing Surface Water Tax revenues and to find out the factors that became obstacles in efforts to increase Surface Water Tax revenues. This qualitative research method the author uses data collection techniques in the form of interviews and documentation and then analyzed based on research problems. The theory used in this research is the theory of intensification and extensification. To be able to answer these problems the researchers used a qualitative method with an interactive model. The results of this study indicate that the Efforts to Increase Surface Water Tax Revenue by the Regional Revenue Agency of Riau Province have not gone well, this is caused by several factors that hinder the implementation of efforts to increase surface water tax revenues, namely the existence of measuring instruments that do not function until taxpayers do not use measuring tool in calculating the use of surface water. Keywords : Effort, Local Tax, Surface Water Tax, Regional Revenue Agency, Intensification and Extensification